Lay Conceptions of Happiness: Associations With Reported Well-Being, Personality Traits, and Materialism - Joshanloo, Mohsen (Frontiers in Psychology, 2019)
Lay conceptions of happiness are beliefs about the nature, value, antecedents, and outcomes of happiness. Happiness research has largely focused on the levels, predictors, and outcomes of happiness, and conceptions of happiness have received less attention. This study sought to expand our understanding of these conceptions by examining a relatively large number of them (i.e., eudaimonism, inclusive happiness, externality of happiness, fear of happiness, transformative suffering, fragility of happiness, valuing happiness, and inflexibility of happiness), in samples from Korea and Canada. Five components of well-being (i.e., social well-being, psychological well-being, life satisfaction, positive affect, and negative affect), the Big Five personality traits, materialism, and demographic variables were measured in addition to conceptions of happiness. The results showed that conceptions of happiness predicted various components of well-being over and above personality traits and demographic variables. These conceptions contributed additional variance to the prediction of materialism. The conceptions were largely independent of personality traits; there were gender and age differences in the conceptions of happiness. The results also suggest that two dimensions of “effortful virtuosity vs doubtful pursuit” and “malleability vs stability” are the underlying dimensions along which the conceptions of happiness vary. There were similarities and differences in the results for Korea and Canada. In sum, this study provides a relatively comprehensive and systematic exploration of the conceptions of happiness, their structure, nomological network, and their relevance to well-being research. It is hoped that these results will stimulate more research on lay conceptions of happiness.